1987
DOI: 10.1085/jgp.89.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Convective paracellular solute flux. A source of ion-ion interaction in the epithelial transport equations.

Abstract: An electrolyte model of an epithelium (a cell and a tightjunction in parallel, both in series with a lateral interspace basement membrane) is analyzed using the formalism of nonequilibrium thermodynamics . It is shown that if the parallel structures are heteroporous (i .e ., reflection coefficients for two ion species differ between the components), then a cross-term will appear in the overall transport equations of the epithelium . Formally, this cross-term represents an ion-ion interaction . With respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In the rat, the reflection coefficient of Cl Ϫ (taken to be ϭ 0.30 in the present model) is much smaller than that of other major solutes ( ϭ 0.75-0.90) (49). Thus the model predicts that paracellular convective solute flux contains a disproportionately large amount of Cl Ϫ , which, taken in isolation, raises the transepithelial voltage, enhances paracellular Na ϩ diffusion and thereby increases the metabolic efficiency of Na ϩ transport.…”
Section: Paracellular Water Transport and Metabolic Efficiencymentioning
confidence: 75%
See 1 more Smart Citation
“…In the rat, the reflection coefficient of Cl Ϫ (taken to be ϭ 0.30 in the present model) is much smaller than that of other major solutes ( ϭ 0.75-0.90) (49). Thus the model predicts that paracellular convective solute flux contains a disproportionately large amount of Cl Ϫ , which, taken in isolation, raises the transepithelial voltage, enhances paracellular Na ϩ diffusion and thereby increases the metabolic efficiency of Na ϩ transport.…”
Section: Paracellular Water Transport and Metabolic Efficiencymentioning
confidence: 75%
“…In the rat a significant fraction of water reabsorption is thought to occur paracellularly, as suggested by several studies showing reflection coefficients Ͻ1 for the main solutes (9,12,49,54). The role of paracellular water transport is less clear in the mouse.…”
Section: Paracellular Water Transport and Metabolic Efficiencymentioning
confidence: 99%
“…These models have indicated that paracellular fluxes of Na ϩ and Cl Ϫ constitute an important fraction of their overall reabsorption; that these fluxes assume greater significance later along the tubule (where transepithelial Cl Ϫ and HCO 3 Ϫ gradients are well developed); and that both diffusive and convective components of paracellular Cl Ϫ flux are substantial (45). Nevertheless, these models have supported the primacy of luminal membrane Na ϩ /H ϩ exchange in determining the rate of overall proximal Na ϩ reabsorption (47).…”
mentioning
confidence: 99%
“…the paracellular pathway and the cell) through which water also travels, then cross-terms in overall (or “composite”) epithelium system equations can still occur. These represent formal ion-ion interactions and can have important consequences for the interpretation of tracer flux experiments and determination of permeabilities (Weinstein, 1987). Since in our model we assume a fully transcellular pathway for water (consistent with the assumption of an osmotic mechanism as discussed in the introduction), these formal composite-system interactions are not present (Weinstein, 1987; Friedman, 2008).…”
Section: Discussionmentioning
confidence: 99%